PERILAKU PETERNAK SAPI PERAH DALAM MENANGANI LIMBAH TERNAK - K Khoiron (Jurnal Ilmu Kesehatan Masyarakat, 2012)
Dairy farming has an important role in daily life of small holders, namelyto provide job opportunity and support the fullfillment of animal protein consumption. However, the waste of such farming could cause environmental pollution and a threat to human health. The study was conducted to analyze the relationship between the behavior of dairy farmers in Junrejo to handle the farm waste and their knowledge, attitude, and infrastructure availability. The study used cross sectional design. The data supporting the study were collected by means of a structured questionnaire, an observation sheet, and an indepth interview instruction.The Results showed that correlation exists between the variables studied and farmers behavior to handle farm waste, namely knowledge (correlation coefficient of 0,762), attitude (0,756), and infrastructure availability (0,727).